Border Disease Virus: An Exceptional Driver of Chamois Populations Among Other Threats - Serrano, Emmanuel; Colom-Cadena, Andreu; Gilot-Fromont, Emmanuelle; Garel, Mathieu; Cabezón, Oscar; Velarde, Roser; Fernández-Sirera, Laura; Fernández-Aguilar, Xavier; Rosell, Rosa; Lavín, Santiago; Marco, Ignasi (Frontiers in Microbiology, 2015)
Though it is accepted that emerging infectious diseases are a threat to planet biodiversity, little information exists about their role as drivers of species extinction. Populations are also affected by natural catastrophes and other pathogens, making it difficult to estimate the particular impact of emerging diseases. Border disease virus genogroup 4 (BDV-4) caused a previously unreported decrease in populations of Pyrenean chamois (Rupicapra p. pyrenaica) in Spain. Using a population viability analysis, we compared probabilities of extinction of a virtual chamois population affected by winter conditions, density dependence, keratoconjunctivitis, sarcoptic mange and BDV outbreaks. BDV-affected populations showed double risk of becoming extinct in 50 years, confirming the exceptional ability of this virus to drive chamois populations.